DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN D-8 COUNTRIES: THE ROLE OF THE CORRUPTION PERCEPTION INDEX (CPI) AS A MODERATING VARIABLE - Agitsna Alya Rizqa; Ghafur Wibowo , Muhammad (Jurnal Bisnis dan Keuangan, 2024)
Foreign investment is pivotal in mitigating inequality within a country, particularly regarding financial aspects. Corruption levels can affect foreign investment flows in multiple ways: it may either deter foreign direct investment by diminishing its appeal to investors or serve as a stimulus to boost such investments. This study enhances understanding by incorporating exports as an independent variable and the Corruption Perception Index (CPI) as a moderating variable, aiming to refine the relationship between economic growth, exchange rates, and exports in influencing foreign direct investment. The research employs panel data regression analysis and moderated regression analysis (MRA) across D-8 countries from 2017 to 2022. Findings indicate that exports significantly impact foreign direct investment, whereas economic growth and exchange rates do not. The CPI moderates the relationship between economic growth and exports on FDI, weakening it, but situs big77 strengthens the link between exchange rates and FDI. Elevated economic growth and high export values imply that investors might resort to bribery to expand their global market share and enhance production processes to satisfy high demand. The stability of the exchange rate mirrors technological advancements, creating a corruption-free virtuous cycle that fosters increased investment.